К вопросу о совершенствовании подготовки и задействования мобильных медицинских формирований ОАО «РЖД» при чрезвычайных ситуациях - Кульбачинский, В.В.; Семенчуков, А.В.; Сахаров, А.В.; Базазьян, А.Г.; Романов, В.В.; Самарин, Д.В. (Актуальні проблеми транспортної медицини, 2010)
Розглянуті основні принципи комплектування, підготовки і задіювання в умовах надзвичайних ситуацій мобільних медичних формувань залізничного транспорту. Показані база формування конкретних сил і засобів, система управління і координації їх діяльності, особливості матеріально технічного забезпечення і виконання завдань по призначенню. Обгрунтовані заходи по подальшому вдосконаленню роботи мобільних медичних формувань. ВАТ «РЖД». The major principles of designation, training and engagement of mobile medical units of railway service in emergency situations are overviewed. The organization, controlling and coordination of medical protection involving required medical services and means are described. Moreover the peculiarities of logistics of medical protection are highlighted as well as the medical task performance for the intended purposes. Measures for further development of mobile medical services performance under the authority of Russian Railways JSC are established.